2011
DOI: 10.1016/j.yexcr.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

KSR1 is a functional protein kinase capable of serine autophosphorylation and direct phosphorylation of MEK1

Abstract: The extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) pathway is a highly conserved signaling pathway that regulates diverse cellular processes including differentiation, proliferation, and survival. Kinase suppressor of Ras-1 (KSR1) binds each of the three ERK cascade components to facilitate pathway activation. Even though KSR1 contains a C-terminal kinase domain, evidence supporting the catalytic function of KSR1 remains controversial. In this study, we produced recombinant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 72 publications
0
27
2
Order By: Relevance
“…A functional catalytic lysine appears to be absent from KSR, unlike what we found in WNK protein kinases; in WNKs the catalytic lysine is not in the canonical position, but it is nearby in a distinct structural element [33]. Nevertheless, KSR1 purified from E. coli can directly phosphorylate MEK1 in vitro, albeit at a rate that may be representative of a catalytically impaired Raf mutant [29]. Regardless, KSR is a critical component of the MAPK pathway and thus subject to modulation just as are the other proteins in the pathway.…”
Section: Kinase Suppressor Of Rascontrasting
confidence: 50%
See 2 more Smart Citations
“…A functional catalytic lysine appears to be absent from KSR, unlike what we found in WNK protein kinases; in WNKs the catalytic lysine is not in the canonical position, but it is nearby in a distinct structural element [33]. Nevertheless, KSR1 purified from E. coli can directly phosphorylate MEK1 in vitro, albeit at a rate that may be representative of a catalytically impaired Raf mutant [29]. Regardless, KSR is a critical component of the MAPK pathway and thus subject to modulation just as are the other proteins in the pathway.…”
Section: Kinase Suppressor Of Rascontrasting
confidence: 50%
“…Glucose-induced insulin gene transcription has been shown to require a set of core transcription factors, including BETA2 (also known as NeuroD1), PDX1, MafA, and NFAT [29,[40][41][42][43][44][45][46]. We showed that these transcription factors act synergistically to promote insulin gene transcription in an ERK1/2-dependent manner, as phosphorylation of both Beta2 and PDX-1 is direct [47].…”
Section: Glucose Metabolism and Mapk Activationmentioning
confidence: 82%
See 1 more Smart Citation
“…Omg is expressed primarily in neural tissues and is required for myelination in the central nervous system. Ksr1 promotes oncogenic RAS and MAPK signaling in mice and cells, so its deletion would be expected to actually inhibit tumor growth (Lozano et al 2003;Goettel et al 2011). WSB1 appears to participate in an E3 ubiquitin ligase complex not known to be associated with cancers.…”
Section: Resultsmentioning
confidence: 99%
“…At that time, when the KSR1 function was considered only in scaffolding of MAPK components, the loss of signalling at supra-physiologic KSR1 expression levels was proposed to be due to the titration of pathway members away from each other, a phenomenon termed as "combinatorial inhibition" [54]. However, emerging evidence suggests that KSR1 possesses dual activity as a scaffold protein and maybe also as active kinase phosphorylating C-RAF and MEK [17,[57][58][59]. Moreover, KSR1 can also form dimers with RAF and modulate its activity adding complexity to the simple view of KSR1 scaffolding function [17][18].…”
Section: Discussionmentioning
confidence: 99%